N-Linked Glycosylation Protects Gammaretroviruses against Deamination by APOBEC3 Proteins - Rosales Gerpe, María Carla (J Virol, 2014)
Retroviruses are pathogens with rapid infection cycles that can be a source of disease, genome instability, and tumor development in their hosts. Host intrinsic restriction factors, such as APOBEC3 (A3) proteins, are constitutively expressed and dedicated to interfering with the replication cycle of retroviruses. To survive, propagate, and persist, retroviruses must counteract these restriction factors, often by way of virus genome-encoded accessory proteins. Glycosylated Gag, also called glycosylated Pr80 Gag (gPr80), is a gammaretrovirus genome-encoded protein that inhibits the antiretroviral activity of mouse A3 (mA3). Here we show that gPr80 exerts two distinct inhibitory effects on mA3: one that antagonizes deamination-independent restriction and another one that inhibits its deaminase activity. More specifically, we find that the number of N-glycosylated residues in gPr80 inversely correlates with the sensitivity of a gammaretrovirus to deamination by mouse A3 and also, surprisingly, by human A3G. Finally, our work highlights that retroviruses which have successfully integrated into the mouse germ line generally express a gPr80 with fewer glycosylated sites than exogenous retroviruses. This observation supports the suggestion that modulation of A3 deamination intensity could be a desirable attribute for retroviruses to increase genetic diversification and avoid immune detection. Overall, we present here the first description of how gammaretroviruses employ posttranslational modification to antagonize and modulate the activity of a host genome-encoded retroviral restriction factor. IMPORTANCE APOBEC3 proteins are host factors that have a major role in protecting humans and other mammals against retroviruses. These enzymes hinder their replication and intensely mutate their DNA, thereby inactivating viral progeny and the spread of infection. Here we describe a newly recognized way in which some retroviruses protect themselves against the mutator activity of APOBEC3 proteins. We show that gammaretroviruses expressing an accessory protein called glycosylated Gag, or gPr80, use the host's posttranslational machinery and, more specifically, N-linked glycosylation as a way to modulate their sensitivity to mutations by APOBEC3 proteins. By carefully controlling the amount of mutations caused by APOBEC3 proteins, gammaretroviruses can find a balance that helps them evolve and persist.